If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5) + -5x = 3 Reorder the terms: 3(5 + x) + -5x = 3 (5 * 3 + x * 3) + -5x = 3 (15 + 3x) + -5x = 3 Combine like terms: 3x + -5x = -2x 15 + -2x = 3 Solving 15 + -2x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -2x = 3 + -15 Combine like terms: 15 + -15 = 0 0 + -2x = 3 + -15 -2x = 3 + -15 Combine like terms: 3 + -15 = -12 -2x = -12 Divide each side by '-2'. x = 6 Simplifying x = 6
| 3x+4=x+-8 | | 1.1y+1.2x-5.4=-10 | | 4x^2-86x+37=4x^2-6 | | 3-12+10=8-2x | | X(3x+11)-20=0 | | x+3.1=5.4 | | 8d-onethird(6-9d)=42 | | 9(x+4)=41 | | X(3x-7)+6=0 | | Q(r)=3r^2-21r+30 | | 180m=25x+10y | | 180=25x+10y | | -16t^2+29t+6=h | | -7x^2-3y=-4xy+5 | | -6n-9m-m-3n= | | 3h=25x+10y | | (x^2+8x-7)(x^2+9x-5)= | | 1000=x^3+11x^2+24x | | 8n^2+6n-1224=0 | | -9x+13y-3y+5x= | | 5-(3b-5)=-17 | | (X*4)+(y*2)=360 | | 9=r+7 | | 8x-4y=-1 | | 6x+4x-45=60-5x | | 51-5x=19+11x | | 5r+11-2r-1= | | -23=-6p-7p | | 3z+4=4 | | 0=4.9t^2-11t-92 | | 23x+4(x+1)=27(x+1)-23 | | 4x+3(4x+7)=133 |